The Effect of Genetic Polymorphisms in SLCO2B1 on the Lipid-Lowering Efficacy of Rosuvastatin in Healthy Adults with Elevated Low-Density Lipoprotein - Kim, Tae-Eun; Shin, Dongseong; Gu, Namyi; Jung, Byung Hwa; Kim, Jayoun; Cho, Young Min; Yu, Kyung-Sang; Cho, Joo-Youn (WILEY, 2017)
Rosuvastatin is an HMG-CoA reductase inhibitor widely used for treating hypercholesterolaemia. We investigated whether genetic polymorphisms in solute carrier organic anion transporter 2B1 (SLCO2B1) affect the lipid-lowering effect of rosuvastatin in healthy adults with elevated low-density lipoprotein (LDL). This study included 18 volunteers with LDL levels above 130 mg/dL. Rosuvastatin (20 mg) was administered once a day for 8 weeks. Blood samples were drawn before and after the 8-week treatment to measure changes in lipid levels. The presence of single nucleotide polymorphisms (SNPs) of SLCO2B1 (c.935G>A and c.1457C>T), SLCO1B1 (c.521C>T, c.388A>G and c.-11187G>A) and ABCG2 (c.421C>A) was determined by genotyping. Responses to rosuvastatin were compared between wild-type and variant genotypes using permutation test on each polymorphism. In volunteers with SLCO2B1 c.935G>A (rs12422149) variant, rosuvastatin was less effective at lowering LDL (mean % decrease: GG 62.8% GA 50.6% AA 49.3%, p = 0.012) and apoprotein B (mean % decrease: GG 52.1% GA 42.8% AA 42.8%, p = 0.036). Regarding SLCO2B1 c.1457C>T (rs2306168) SNP, there was no significant difference between wild-type and variant genotypes. This study demonstrated that SLCO2B1 c.935G>A (rs12422149) polymorphism influenced the lipid-lowering effects of rosuvastatin in volunteers with hypercholesterolaemia.
Keywords: PLASMA-CONCENTRATIONS; ABCG2 POLYMORPHISM; APPLE JUICE; PHARMACOKINETICS; MONTELUKAST; CHINESE; SLCO1B1; TRANSPORTERS; FEXOFENADINE; VARIANT